Some Problems in Recording and Analyzing South African English Vocabulary (The Experiences of an Outsider) - Gold, David L. (Lexikos, 1994)
This article describes some problems in collecting and studying South African English vocabulary on the basis of non-South-African texts faced by a linguist who is a native speaker of American English. The questions are thus: Are non-South-African texts just as reliable as South African texts? More reliable? Less reliable? And is a linguist who is a native speaker of a different variety of English just as reliable as a native? More reliable? Less reliable? It is suggested here that the best way of studying a language, if possible, is by having both insiders and outsiders look at the material. Keywords: abbreviations, african languages, afrikaans, american english, australian english, black english, british english, canadian english, capitalization, careful use of primary and secondary sources, convergence, definitions, dictionaries, differential dictionaries, dutch, english, etymology, family names, folk etymology, french, german, hebrew, initialisms, latin, lexicography, misprints, nonce forms, overdefinition, personal names, place names, postal terms, prepositions, productivization, reflexive pronouns, slang, slips of the tongue, south african english, spelling, status and usage labels, surfers' terms, teamwork, underdefinition, yiddish, zoological terms